Ironic processes of concentration and suppression under pressure: A study on rifle shooting in Norwegian elite biathletes - Bartura, K., Abrahamsen, F. E.; Gustafsson, H.; Hatzigeorgiadis, A.; Gorgulu, R. (Scandinavian Journal of Medicine & Science in Sports, 2024)
In rifle shooting, suppressing unwanted thoughts can backfire in one's performance, causing athletes to behave contrary to their desired intention and further deteriorate their performance. Purpose This study examined how priming attentional and negative cues affected participants' shooting performances toward ironic error targets under cognitive load conditions in Stroop task across two experiments. Methods Semi-elite biathletes (Experiment 1, n = 10; Experiment 2, n = 9) participated in the study. The study used a within-subject quasi-experimental design, particularly a one-way repeated measures multivariate analysis of variance and a 2 × 2 fully repeated measures analysis of variance, to determine the participants' hit rates and shooting response times (RTs). In both experiments, the participants completed the reverse-Stroop-based target shooting performance under low- and high-cognitive load conditions while receiving frequent priming attentional and negative cues. Results The findings from Experiment 1 suggest that regulating repetitive priming attentional thoughts is efficacious in mitigating the likelihood of ironic performance errors and interference effects. The results of Experiment 2 show that repetitive priming negative cues resulted in negligible ironic error hit rates and slower RTs in target hits under high-cognitive load conditions. The Bayesian analyses provided evidence supporting the null hypotheses. Conclusion Trying to control repetitive priming attentional and negative thoughts reduces ironic performance errors to a similar degree under cognitive load conditions among biathletes, regardless of interference effects. Further research is needed to determine the effectiveness of suppressing task-relevant negative instructions in reducing the likelihood of ironic performance errors under pressure.